When Shari'a governs: the impasse of religious relations in Sudan - Mahmoud, Mohamed (Islam and Christian-Muslim relations, 2007)
The rapid political rise of the National Islamic Front is examined within a broader and more complex context, particularly as it pertains to relations between Muslims and non-Muslims in Sudan during the period from 1989 to the present. The regime's decision to change the nature of the South–North conflict into a jihad confrontation was determinative for the future of Islam in the Sudan, even though the regime's jihad discourse has been characterized by ambiguity and confusion. The Islamists have not produced a policy statement or a juristic work addressing the status of non-Muslims in the Sharica-based state and society they envisage, in spite of the 1991 Criminal Act and the 1998 Constitution of the Republic of Sudan. As a result, non-Muslims in Sudan are facing a difficult and testing time.